UPAYA USTADZAH DALAM MENINGKATKAN KEMAMPUAN BACA AL-QUR’AN DI RUMAH QUR’AN AKHLAQ MULIA - Asmawati Asmawati (Tarbiya Islamica, 2014)
The purpose of this study was to determine the understanding of the cleric's efforts in improving the ability to read the Qur'an at the Akhlak Noble Qur'an House, then the supporting and inhibiting factors faced by the Noble Qur'an Akhlak House in Improving the Ability to Read the Qur'an, Data collection techniques used are observation, interviews, and documentation. The data analysis collection techniques used are data collection techniques, data analysis techniques, data reduction, data display, drawing conclusions. The results of the research carried out showed that: 1) The efforts of Akhlaq Mulia Qur'an House in improving the ability to read the Qur'an by introducing the Qur'an to early childhood by introducing students through memorizing the Qur'an, memorizing together, teach iqra' first and then proceed to reading juz, teach short suras, daily prayers, provide motivation about rewards and rewards for readers and memorizers of the Qur'an and use various methods such as learning methods Iqra and murajaah: 2) Supporting factors in efforts to improve the ability to read the Qur'an are high interest in learning, motivation from educators and exemplary traits reflected by educators. While the inhibiting factors are students who are difficult to manage, discipline, the negative influence of the environment and the negative influence of information technology such as gadgets and game applications, as well as the methods used by educators in teaching the Qur'an.